Dietary B vitamins and glioma: A case–control study based on Chinese population - Zhang, Weichunbai; Jiang, Jing; Kang, Xun; Wang, Ce; Chen, Feng; Zhang, Botao; Li, Shenglan; Huang, Sijie; Li, Wenbin (Frontiers in Nutrition, 2023)
Background: Dietary antioxidants have long been thought to be likely to prevent the development of gliomas. Previous studies have reported vitamin A, C, and E protective effects against gliomas. B vitamins, one of the main vitamins in the diet, are closely related to human health, but the association with gliomas has rarely been reported. Objective: This study aimed to evaluate the relationship between five B vitamins and glioma. Methods: In this Chinese population-based case-control study, 506 glioma cases and 506 matched (age and sex) controls were included. The dietary intake of study participants was assessed using a valid 111-item food frequency questionnaire. The intake of five B vitamins was calculated based on participants’ dietary information from the food frequency questionnaire. The logistic regression model was used to examine the association between B vitamins and glioma, and the restriction cubic spline evaluated the dose-response relationship between the two. Results: After adjusting for confounding factors, thiamine (OR=0.09, 95%CI: 0.05-0.20), riboflavin (OR=0.12, 95%CI: 0.06-0.25), nicotinic acid (OR=0.24, 95%CI: 0.12-0.47), folate (OR=0.07, 95%CI: 0.03-0.15) and biotin (OR=0.14, 95%CI: 0.07-0.30) in the highest tertile were associated with a significantly decreased risk of glioma compared with the lowest tertile. The results of thiamine and biotin in glioma with different pathological types and grades were different. The restricted cubic spline function showed significant dose-response relationships between the intake of five B vitamins and the risk of glioma. When B vitamins exceeded a specific intake, the risk of glioma did not change. Conclusion: Our study suggests that higher dietary intake of thiamine, riboflavin, nicotinic acid, and folate are associated with a decreased risk of glioma, but the results of biotin are not consistent among different populations. In the future, prospective studies should be conducted better to validate the effects of B vitamins on gliomas.